‘From Rubber to Oil Palm’: Livelihood Structural Transformation of Local and Transmigrant Farmer Households in Minangkabau - Wati, Elva; Dharmawan, Arya Hadi; Damanhuri, Didin S; Sumarti, Titik (Sodality: Jurnal Sosiologi Pedesaan, 2019)
This study aims to analyze the transformation of livelihood structures in local and transmigrant farmer households that occur due to the entry of oil palm. Oil palm has become a new agricultural commodity that it is believed to provide better income for farmers. This research was conducted with a quantitative and qualitative approach. Quantitative data collection was carried out through a survey of 63 farm households. Meanwhile, qualitative data collection was carried out through in-depth interviews. The results of the study indicate that the transformation of rubber commodities to oil palm in general supports the economy of farmer households, which are income increases, livelihood diversity, and welfare increases. In addition, the transformation also has an impact on consumptive and materialistic lifestyle changes in farm households and the formation of farmer household typologies based on post-transformation livelihoods.